Impact of the pulse width modulation on the temperature distribution in the armature of a solenoid valve - Goraj, Robert (Zielona Góra: Uniwersytet Zielonogórski)
In order to estimate the inductive power set in the armature of the high-speed solenoid valve (HSV) during the open loop control (OLC) using pulse width modulation (PWM) an analytical explicit formula has been derived. The simplifications taken both in the geometry and in the physical behavior of HSV were described. The inductive power was calculated for different boundary conditions and shown as a function of the frequency of the coil current.
Keywords: solenoid valve; armature; inductive power; PWM; temperature